The potential for quality production in birch stands in north-eastern China using different precommercial thinning strategies - Samuelsson, Fredrik (SLU/Southern Swedish Forest Research Centre, 2006)
China constitutes 20% of the world's population. China is a large importer of forest products and a great consumer of paper and the consumption tends to increase with the growing Chinese economy. China will also become an important producer of forest products. Therefore it is important for the Swedish forest sector to learn more about China. The purpose of this thesis was to investigate the potential for using Swedish precommercial thinning strategies as an instrument to influence the properties of white birch (Betula platyphylla) stands in north-eastern China, with emphasis on quality related properties. The quality related properties were defined in cooperation with IKEA to investigate if it is possible to produce birch of a quality that follows the requirements of IKEA. The investigation was done with simulated precommercial thinning experiments in young birch stands in north-eastern China, along with a study of Swedish and Chinese literature within the subject. The field work was carried out within the Ta He forest bureau in the Heilongjiang province. The stand age in the investigated stands ranged from 9 to 18 years and the majority of the stands were naturally regenerated with white birch after a big forest fire. The stem density after the simulated precommercial thinning were set to1500 and 3000 stems per hectare in order to cover the greater part of the recommendations used for birch in Sweden. The results indicate that it is possible to influence the quality through selective precommercial thinning, but it should be noticed that the quality improvements were minor. Before precommercial thinning the share of stems with quality faults were 40 % and after the simulated thinnings to 1500 and 3000 stems per ha the corresponding numbers were 34 % and 36 %, respectively. The simulated thinnings also resulted in an increased mean height and diameter and the quotient between height and diameter was reduced. However, this study only deals with the immediate effects of stem selection and does not consider the long-term effects on stand development. The conclusion is that there are both knowledge and potential for quality production of birch, but the interest for birch is rather sparse in this part of China due to logging bans, inferior volume production and to the forest ownership structure.